Cancer care beyond the clinic: An analysis of participation at The Gathering Place, a stand-alone cancer support community. Issue 28 (1st October 2022) - Mitchell, Carley; Apisdorf, Cheryl; Bennett, Beth; Hsu, Melinda Laine
Abstract : 214 Background: A wealth of published data exists highlighting the benefits of alternative and supportive therapies when used in combination with traditional medical approaches for individuals diagnosed with cancer. Many physical and emotional symptoms, along with quality of life, can be improved through exercise, artistic expression, mind-body practices and support group participation. While many of these services are offered through healthcare systems or large national foundations, fewer community-run organizations exist. The Gather Place (TGP) uniquely serves the Greater Cleveland area at two stand-alone locations. A wide variety of programs and services are offered, free-of-charge, to those affected by cancer. Since spring of 2020, most services have been provided virtually due to the COVID-19 pandemic. While few studies have evaluated predictors of support group utilization, there is limited data on the demographics of participants at individual support communities. Methods: De-identified, retrospective data was gathered from 04/01/2021 to 03/31/2022. Participant data including age, gender, ethnicity, residential zip code, cancer type, treatment center, date of first attendance, programs attended, and frequency of program attendance were collected and analyzed. Results: 1, 494 participants with cancer utilized services at TGP with varying rates of unknown data among each category. Educational opportunities, support groups and one-on-one emotional support sessions were most frequently attended. Female involvement was greater than males (83.9% v. 15.7%), with higher participation among Caucasians compared to African Americans (79.5% v. 16.2%). 67.1% of participants resided in zip codes above the median household income of Cuyahoga County. Participants with breast and gynecologic cancers made up the majority (44.3% & 10.1%), while those with cutaneous, head/neck and hepatobiliary malignancies comprised the smallest distribution (1.6%, 1.7% & 1.8%). Conclusions: TGP is a unique organization unaffiliated with a major healthcare system providing nutrition, fitness, healing arts, education and individual/group support programs. Despite a high incidence of prostate and lung cancer diagnoses in Northeast Ohio, participants with these malignancies were a small percentage of total attendees, differing from the high disease incidence and program participation seen in patients with breast cancer. As information was gathered solely during the COVID-19 pandemic when program delivery shifted to the virtual setting, racial or income disparities reported here may reflect similar disparities seen in tele-health during the pandemic. The gaps in utilization we identified highlight opportunities for targeted areas of improved education and referral.